Peran Audit Internal dalam Meningkatkan Kinerja Bank Syariah - Aisyah Naila Ashfa; Zahra Maylani; Alfi Nurmalinda; Zahrotus Saniyah; Ika Nurfitriani (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
This study aims to evaluate the strategic function of internal audit in improving operational efficiency and achieving targets in Islamic banking institutions. Utilizing qualitative methods and a literature review approach, this study analyzed secondary data from books, scholarly articles, and governance reports of Islamic banks with significant assets in Indonesia. The research findings indicate that internal audit in Islamic banks has a dual role, serving as a provider of assurance and consulting services to mitigate operational and financing risks, while also serving as a supervisor of Sharia compliance. Document analysis revealed that Bank Syariah Mandiri and Bank Muamalat Indonesia have formalized this function as a value-added component of the organization, while Bank BNI Syariah and Bank BRI Syariah have not explicitly stated it in their governance reports during the period analyzed. From this, it can be concluded that independent and competent internal audit, with full support from top management, contributes significantly to improving the financial and non-financial performance of Islamic banks.